Revealing Size Dependent Structural Transitions in Supported Gold Nanoparticles in Hydrogen at Atmospheric Pressure. Issue 51 (10th November 2021) - Nassereddine, Abdallah; Wang, Qing; Loffreda, David; Ricolleau, Christian; Alloyeau, Damien; Louis, Catherine; Delannoy, Laurent; Nelayah, Jaysen; Guesmi, Hazar
Abstract: The enhancement of the catalytic activity of gold nanoparticles with their decreasing size is often attributed to the increasing proportion of low‐coordinated surface sites. This correlation is based on the paradigmatic picture of working gold nanoparticles as perfect crystal forms having complete and static outer surface layers whatever their size. This picture is incomplete as catalysts can dynamically change their structure according to the reaction conditions and as such changes can be eventually size‐dependent. In this work, using aberration‐corrected environmental electron microscopy, size‐dependent crystal structure and morphological evolution in gold nanoparticles exposed to hydrogen at atmospheric pressure, with loss of the face‐centered cubic crystal structure of gold for particle size below 4 nm, are revealed for the first time. Theoretical calculations highlight the role of mobile gold atoms in the observed symmetry changes and particle reshaping in the critical size regime. An unprecedented stable surface molecular structure of hydrogenated gold decorating a highly distorted core is identified. By combining atomic scale in situ observations and modeling of nanoparticle structure under relevant reaction conditions, this work provides a fundamental understanding of the size‐dependent reactivity of gold nanoparticles with a precise picture of their surface at working conditions. Abstract : Atomic‐resolution transmission electron microscopy reveals size‐dependent structural transformations in supported gold nanoparticles upon exposure to hydrogen at atmospheric pressure. Molecular dynamics simulations highlight the role of mobile gold atoms in the evolution of particle crystal structure and morphology observed below 4 nm and unveil the unique atomic and electronic structures of hydrogenated gold nanoparticles in this critical size regime.